Musicalidades em baladas, canções, elegias e rondós de Manuel Bandeira - Brunet, Jacqueline Nunes (2024)
This research aims to comprehend the expression of literary musicalities in the modern lyrical forms of ballad, song, elegy, and rondo by Manuel Bandeira, and his effective contribution to the interdisciplinary field of poetry and music. We understand musicalities as the rhythmic and fluid product of working with sounds, images, and meanings of the signifier(s) in poetic language. To achieve this objective more broadly, a historical study of the connections between poetry and music was conducted within the Western branch, along with a diachronic study of works and precursors of lyrical forms, and a comparative analysis of each lyrical form, resulting in a corpus of twenty-nine poems. To conclude, we sought to establish connections between Bandeira’s poetics and music. This study, as a product of participation in the research group V!VA, Poesia II, was designed to fill gaps regarding the understanding of the sonorities of Bandeira’s poems. The analyzes have as a theoretical contribution contents sensitive to the relationship between language and musicality, such as those of Henri Meschonnic (1998) in the treatment of rhythm; Alfredo Bosi (1977) regarding sound temporality; Murray Schafer (1991) regarding intonation; and Nilce Martins (2008) on the expressiveness of phonemes. In the end, we confirmed that the resources that make up the implied musicalities (elements of rhythm and intonation) and the use of popular language represent the poetic-musical aspect that was so appealing to composers of Bandeira’s time and subsequent periods, which made our poet the most musical of his generation